2016
DOI: 10.1002/chem.201602816
|View full text |Cite
|
Sign up to set email alerts
|

New Insight in Copper‐Ion Binding to Human Islet Amyloid: The Contribution of Metal‐Complex Speciation To Reveal the Polypeptide Toxicity

Abstract: Type-2 diabetes (T2D) is considered to be a potential threat on a global level. Recently, T2D has been listed as a misfolding disease, such as Alzheimer's and Parkinson's diseases. Human islet amyloid polypeptide (hIAPP) is a molecule cosecreted in pancreatic β cells and represents the main constituent of an aggregated amyloid found in individuals affected by T2D. The trace-element serum level is significantly influenced during the development of diabetes. In particular, the dys-homeostasis of Cu(2+) ions may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 101 publications
(591 reference statements)
2
22
0
Order By: Relevance
“…Although excess of intracellular Zn can trigger oxidative stress from mitochondria and lead to neuronal degeneration (57), Zn has previously been shown to have beneficial effects on glycemic control as well as aging, immunity, and oxidative stress (58), whereas serum Cu is associated with higher HbA1c levels (31, 59). Experimental studies have shown that the amino acids residues involved in Cu coordination complexes have a key role in the formation of human islet amyloid peptide aggregation, which alters the autophagy pathway in pancreatic β-cells and leads to the development of diabetes (19, 20). The actions of Zn and Cu in glucose metabolism appear to be antagonistic; hence, the balance between Zn and Cu ion concentrations is important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although excess of intracellular Zn can trigger oxidative stress from mitochondria and lead to neuronal degeneration (57), Zn has previously been shown to have beneficial effects on glycemic control as well as aging, immunity, and oxidative stress (58), whereas serum Cu is associated with higher HbA1c levels (31, 59). Experimental studies have shown that the amino acids residues involved in Cu coordination complexes have a key role in the formation of human islet amyloid peptide aggregation, which alters the autophagy pathway in pancreatic β-cells and leads to the development of diabetes (19, 20). The actions of Zn and Cu in glucose metabolism appear to be antagonistic; hence, the balance between Zn and Cu ion concentrations is important.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of Cu homeostasis induces oxidative damage by free radicals; such Cu toxicity is associated with disrupted lipid metabolism, hepatic disorders, neurodegenerative disorders, and atherogenesis (17, 18). Cu ion may also play a protective role in the accumulation of human islet amyloid peptide, which is the major component of amyloid deposits in pancreatic β-cells of type 2 diabetic patients; however, whether or not Cu have a protective role in the etiology of type 2 diabetes is not clarified (19, 20). Excess of Cu under inflammatory conditions trigger oxidative stress which are present in chronic diseases (21).…”
Section: Introductionmentioning
confidence: 99%
“…23 On the other hand, the binding of redox-active Cu(II) to the amyloid peptide could form the peptide-copper complexes, which can stimulate the production of ROS in a toxicity manner. [24][25][26] The resulting ROS, such as H 2 O 2 and OHc would damage DNA, lipids and proteins and thus trigger apoptotic cell death. While some studies report that the Cu(II)-hIAPP complexes produce hydrogen peroxide to a lesser extent than free Cu(II) in solution, suggesting the sacricial protective roles for hIAPP coexisted with Cu(II) in high concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This value suggests that a carbonyl oxygen donor atom may be involved in copper binding, as found for analogous copper species formed with other linear peptides [32]. …”
Section: Resultsmentioning
confidence: 79%